Factors influencing polyautoimmunity in systemic lupus erythematosus (2010)
Objective: Since characterization of the extent to which particular combinations of autoimmune diseases (ADs) occur in excess of that expected by chance may offer new insights into possible common pathophysiological mechanisms, polyautoimmunity (i.e., ADs co-occurring within patients) in systemic lupus erythematosus (SLE) and its associated factors were investigated. Methods: This was a cross-sectional study in which 335 consecutive patients with SLE and the history of 22 ADs were investigated. A multivariate analysis was performed. A systematic literature review was done and results were grouped by hierarchical cluster procedure analysis. Results: There were 136 (41%) SLE patients presenting with at least one other AD. A total of 191 ADs were observed, of which the most frequent were autoimmune thyroid disease (AITD), antiphospholipid syndrome (APS) and Sjögren's syndrome (SS), registered in 60 (18%), 48 (14%) and 47 (14%) cases, respectively. Out of a total number of 1515 SLE patients with polyautoimmunity (1379 reported previously and 136 informed here) there were 77 (5.1%) cases with multiple autoimmune syndrome (i.e., two or more ADs in addition to SLE). Female gender, articular involvement, familial autoimmunity, anti-Ro positivity and patient's origin were risk factors for polyautoimmunity while the presence of anti-RNP antibodies was protective. Four clusters of ADs were found. The most hierarchical one was composed of AITD, APS, SS, and systemic sclerosis. Conclusion: Polyautoimmunity is frequent in SLE, and it is influenced by clinical and immunological features. These findings support that clinically different autoimmune phenotypes might share common susceptibility variants. © 2009 Elsevier B.V. All rights reserved.